NOL6 Regulates the Proliferation and Apoptosis of Gastric Cancer Cells via Regulating TP53I3, CDK4 and MCM7 Expression - He, Lei; Qian, Xiaohan; Ge, Pingping; Fan, Dong; Ma, Xiang; Wu, Qiong; Sun, Jin; Yang, Lihua; Shen, Jian; Xu, Lijian (Frontiers in Oncology, 2022)
Background Gastric cancer (GC) is a prevalent cancer with high mortality and strong invasiveness, and the entire regulatory networks of GC is still unclear. Objective The aim of this study was to explore the specific mechanism of the effect of nucleolar protein 6 (NOL6) on the proliferation and apoptosis of GC cells. Methods The human gastric adenocarcinoma cell line HGC-27 and AGS were cultured. qRT-PCR was used to verify the expression level of NOL6 in GC cells; MTT and EdU were used to test cell proliferation; TUNEL staining and Flow cytometry were used to detect cell apoptosis; The downstream genes and pathways following NOL6 knockdown were explored through the microarray assay and ingenuity pathway analysis, and the downstream genes were finally verified by qRT-PCR and Western blotting. The xenograft mice were used to investigate the effect of NOL6 on GC in vivo. Results TCGA data analysis showed that NOL6 expression level was higher in GC cells than adjacent normal cells. Over-expression of NOL6 increased proliferation and colony formation, and inhibited the apoptotic rate in AGS and HGC-27 cells, while NOL6 knockdown induced the opposite effects. Through microarray assay and IPA analysis, NOL6-related downstream genes and critical signaling pathways were found. And we verified the relationship between downstream genes and GC. Additionally, NOL6 knockdown could decrease the weight and volume of tumor in the mice. Conclusion NOL6 knockdown could inhibit cell proliferation and induce cell apoptosis of GC, suggesting that NOL6 may serve as a potential therapeutic target for treating GC.